Quantification of pleural effusion on CT by simple measurement - Hazlinger, Martin; Čtvrtlík, Filip; Langová, Kateřina; Heřman, Miroslav (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2014)
AIMS: To find the simplest method for quantifying pleural effusion volume from CT scans. METHODS: Seventy pleural effusions found on chest CT examination in 50 consecutive adult patients with the presence of free pleural effusion were included. The volume of pleural effusion was calculated from a three-dimensional reconstruction of CT scans. Planar measurements were made on CT scans and their two-dimensional reconstructions in the sagittal plane and at three levels on transversal scans. Individual planar measurements were statistically compared with the detected volume of pleural effusion. Regression equations, averaged absolute difference between observed and predicted values and determination coefficients were found for all measurements and their combinations. A tabular expression of the best single planar measurement was created. RESULTS: The most accurate correlation between the volume and a single planar measurement was found in the dimension measured perpendicular to the parietal pleura on transversal scan with the greatest depth of effusion. Conversion of this measurement to the appropriate volume is possible by regression equation: Volume = 0.365 × b(3) - 4.529 × b(2) + 159.723 × b - 88.377. CONCLUSION: We devised a simple method of conversion of a single planar measurement on CT scan to the volume of pleural effusion. The tabular expression of our equation can be easily and effectively used in routine practice.
Keywords: pleurální výpotek; Image Processing, Computer-Assisted; tomografie spirální počítačová; Tomography, Spiral Computed; Pleural Effusion; Humans; lidé; počítačové zpracování obrazu